Alterations in serum and intestinal ACE2 in Inflammatory Bowel Disease and the impact of inflammation - Jones, Fiona; Egan, Ciara; Tosetto, Miriam; Strowitzki, Moritz; Kierans, Sarah J.; Rowan, Catherine; Walshe, Margaret; Ryan, Elizabeth; Sheridan, Juliette; Cullen, Garret; Mulcahy, Hugh; Martin, Sean; et al. (Frontiers in Gastroenterology, 2025)
Background/aimsACE2 is highly expressed in the gut and with known alterations in expression in IBD patients potentially linked to gut inflammation and fibrosis. In addition, little is known about the role of serum soluble ACE2 (sACE2) or its hypothetical role in SARS-CoV-2 binding. We sought to evaluate tissue and serum ACE2 profiles in IBD and healthy controls and evaluate alterations related to disease activity and medical therapy.MethodsCirculating sACE2 and intestinal tissue ACE2 was evaluated respectively in serum samples and endoscopic biopsies from patients with IBD and healthy controls in addition to murine DSS induced colitis.Results91 IBD (UC/n=41; CD n=50) and 55 controls were analyzed. Immunohistochemical ACE2 staining in controls was limited to brush border expression with markedly increased colonic ACE2 expression (and reduced ileal ACE2 expression) in IBD. This was not observed in the mouse model which demonstrated positive ileal ACE2 and negative colonic staining in healthy and DSS mice. Colonic ACE2 staining was further increased in Ulcerative Colitis in inflammation (% staining, 20(5-30) vs. 5(0-6.5), p<0.015) and in IBD patients receiving corticosteroids (% staining, 20(20-40) vs 10(0-20), p<0.052). Steroid use was associated with significantly lower sACE2 with a trend towards reduced sACE2 with biologic exposure.ConclusionWe observe significant increases in colonic ACE2 expression in IBD, especially with active colitis. Corticosteroids further modify the observed imbalance between tissue and serum ACE2 levels.